IN SITU HYBRID SPACES AS GENERATIVE SITES FOR TEACHER PREPARATION - Schnellert, Leyton; Kozak, Donna (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2019)
In this study, a university professor and school district literacy coordinator co-designed and co-taught a literacy methods course where teacher candidates participated in dynamic learning in classrooms, exploring how theory can meet practice when students’ funds of knowledge are valued through responsive teaching. Case study methodology was taken up to understand and enhance this in situ teacher education approach. Four themes were derived through qualitative analysis: 1) theory / practice connections in situ; 2) diverse learners and the need for responsivity in teaching; 3) in situ learning through collaboration; and 4) benefits and tensions at the school and program level. Findings suggest that school / university in situ teacher education partnerships can provide rich contextual and situational learning that disrupt normative conceptions of teaching, learning and literacy. DES LIEUX HYBRIDES IN SITU COMME ESPACES CONTRIBUANT À LA FORMATION DES MAITRES Dans le cadre de ce projet de recherche, un professeur d’université et un coordonnateur en littératie au conseil scolaire ont élaboré et enseigné en collaboration un cours en méthodologie d’enseignement de la lecture. Au sein de ce cours, les futurs enseignants ont exploré par un processus d’apprentissage dynamique en classe de quelle manière la théorie s’allie à la pratique lorsque le bagage de connaissances des élèves est sollicité par un enseignement adapté. La méthodologie de l’étude de cas a été utilisée pour comprendre et mettre en valeur cette approche in situ de formation des enseignants. Quatre thèmes ont émergé de l’analyse qualitative : 1) les liens entre la théorie et la pratique in situ, 2) la diversité des apprenants et le besoin d’adaptabilité en enseignement, 3) l’apprentissage in situ par la collaboration et 4) les bénéfices et les tensions au niveau de l’école et du programme. Les conclusions de la recherche démontrent que les partenariats in situ école / université pour former de futurs enseignants peuvent permettre de riches apprentissages en contextes et situations authentiques qui chamboulent les conceptions traditionnelles de l’enseignement, de l’apprentissage et de la littératie.